Single Atom Cocatalysts in Photocatalysis - Wu, Si-Ming; Schmuki, Patrik (Advanced materials (Deerfield Beach, Fla.), 2025)
Single-atom (SA) cocatalysts (SACs) have garnered significant attention in photocatalysis due to their unique electronic properties and high atom utilization efficiency. This review provides an overview of the concept and principles of SA cocatalyst in photocatalysis, emphasizing the intrinsic differences to SAs used in classic chemical catalysis. Key factors that influence the efficiency of SAs in photocatalytic reactions, particularly in photocatalytic hydrogen (H2) production, are highlighted. This review further covers synthesis methods, stabilization strategies, and characterization techniques for common SAs used in photocatalysis. Notably, "reactive deposition" method, which often shows a self-homing effect and thus achieves a maximum utilization efficiency of SA cocatalysts, is emphasized. Furthermore, the applications of SA cocatalysts in various photocatalytic processes, including H2 evolution, carbon dioxide reduction, nitrogen fixation, and organic synthesis, are comprehensively reviewed, along with insights into common artifacts in these applications. This review concludes by addressing the challenges faced by SACs in photocatalysis and offering perspectives on future developments, with the aim of informing and advancing research on SAs for photocatalytic energy conversion.
Keywords: cocatalyst; hydrogen production; single atom; photocatalysis